PAUD Teacher Strategies in Supporting Learning in The Covid-19 Pandemic Period - Fortina Verawati Sianturi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The existence of COVID-19 which still hit Indonesia until in November 2020 had a negative impact on education in Indonesia, especially early childhood education. This makes learning, which was a face-to-face system, must be changed to distance education. In order for learning to continue optimally, of course, the teacher must be able to apply different learning strategies. In the pandemic era, schools implement online learning strategies, including at the Playgroup level. Online learning for children, of course, presents its challenges for the teachers. This study aims to investigate online learning strategies at the playgroup level. Play is also a means for children to channel their great energy and discover new things that were previously unknown in a fun way. And this is certainly different from learning that is understood by adults with all the rules and demands at the end. Playing (while learning) in early childhood has a purpose that adults may not realize, where when a child plays, in fact he is developing the potential that exists within him to become a solid initial capital for himself in the future when facing problems in life. This paper is expected to provide references and education to parents and early childhood teachers in particular to be able to understand the world of early childhood, one of which is by understanding the nature of play and the meaning of play for early childhood. This is obtained by exploring various sources from several literatures from the results of research and thought where the results can be used for early childhood parents and teachers to be more precise in assisting and designing learning for early childhood so that the pearl of early childhood learning, namely playing while learning can be achieved.